"God's Objective Truth, As Far As We Know It": Journalism Ideology at an Evangelical News Magazine - Ferman, David (My University, 2014)
This study mixes interviews and textual analysis to explore the ideology, motivations, routines, and content at WORLD, a major evangelical Christian news magazine whose editor-in-chief, Dr. Marvin Olasky, is a well-known writer and educator. In doing so, the study examines a number of issues, including journalism ideology, the beliefs and motivations of alternative journalists, and the shared beliefs of the “tribe” of American evangelicals. Much of this map of the WORLD ideology is defined by seven themes, among them the concept of the “forgotten man” in American thought and journalism and the need to continue to fight the “culture wars” at the center of the conservative/liberal divide in America. The WORLD journalists are seen as dedicated, talented and passionate writers and editors who consistently cover topics and use sources that the mainstream American press does not. At the same time, Olasky’s concept of “biblical objectivity” as an alternative to mainstream journalism objectivity is found to be imprecise, without a measurable yardstick to how it is implemented. The beliefs of the WORLD writers dovetail almost perfectly with those of traditional evangelicals, and as a result WORLD emphasizes placing God before man-made institutions; the persecution of Christians by multiple groups, including liberals, Muslims and communists, both at home and across the world; the ongoing humanitarian efforts of Christians; the battle being waged against secular/liberal journalism, academia and society, which they believe is destroying America from the inside; and a focus on fighting gay rights and abortion. This first published study of a major evangelical news organization using interviews and textual analysis suggests a number of areas for further research, including how to study writers at other religion-based news organizations and the essential differences between WORLD and other evangelical news sources, such as the more liberal Sojourners magazine. The unique and previously unavailable information in this study is especially relevant at this time in the history of American life and journalism for several reasons, including the ongoing “culture wars” and considerable impact of evangelicals in America, the deepening divide between conservatives and liberals due to beliefs on gay rights and abortion, the declining coverage of religion in the mainstream media, and the influence WORLD has on the evangelical Christian community.
Keywords: Journalism.